Enchanted moours and botija souls: practices, places and cultural connections: Enchanted moours and botija souls: practices, places and cultural connections (Revista de História da UEG (REVHIST), 2024)
Through the convergence of cross-history and micro-history, we access a variety of attributes that configure oral narratives about jar souls and enchanted Moors. We permeate an older cultural substrate of Celtic origin and delve into its peculiar aspects. The narratives date back to the mid-20th century and early 21st century, and deal with subjects who interact with haunting beings from the culture of Ceará and Portugal. As a research objective, we were able to observe a historicity of enchanted Moors and jar souls present in the subjects' narratives, mainly by bringing together a joint contact between the natural and supernatural worlds. The places where they appear gain other meanings when these apparitions manifest, especially when linked to the practices of disenchantment of these beings. The practices of interaction between supernatural beings, places and subjects configured new meanings and historicity’s for this type of narrative.Keywords: Enchanted moors. Souls. Bottles. Disenchantment. Hauntings.